The Effectiveness of Cloze Tests in Assessing the Reading of B2 Level Learners - Bakhronova Makhliyo Akmedovna (Researchparks Publishing, 2022)
The aim of the research is to reveal the positive effect of the use of the cloze test in assessing the reading comprehension of B2level learners in the language learning process. Therefore, this research process analyzes the types of cloze tests and their application, as well as the effect of assessing learners ’reading.